PROGRESSIVE MULTIFOCAL LEUKOENCEPHALOPATHY AS A COMPLICATION OF RITUXIMAB THERAPY FOR RHEUMATOID ARTHRITIS (A CASE REPORT) - I. B. Bashkova; I. V. Madyanov; M. S. Shostak; T. V. Prokopyeva (Научно-практическая ревматология, 2018)
When rheumatoid arthritis (RA) is treated with rituximab (RTM), there may be various adverse events, among which progressive multifocal leukoencephalopathy (PML) occupies a special place. The disease is caused by activation of opportunistic viral (JC-virus) infection in the presence of weakened cellular immunity, which leads to massive demyelination of brain structures. The paper describes a clinical case of using RTM in a female patient with RA with systemic manifestations. This treatment was effective during two years, but multifocal brain damage characteristic of PML developed after the last (fourth) cycle of infusions. Differential diagnosis with other diseases accompanied by similar brain changes allowed the authors to regard PML as the most likely diagnosis in this patient despite the negative result of determining JC virus DNA in blood and spinal fluid. The chosen therapy policy (a reduced dose of glucocorticoids, the use of a serotonin reuptake inhibitor, the antidepressant mirtazapine, and therapeutic plasmapheresis) with regard for presumed PML the patient has been proven to be effective and provided a modest positive trend.